Sweet Corn Cultivation in Odisha - Behera, Manoj Kumar (Indian Farming, 2017)
The story of AntaryamiMajhi, a small farmer from Rasiapali village of Maneswar Block, Sambalpur district of Odisha who is the only farmer from his locality to practice commercial sweet corn cultivation is quite inspiring. With a land area of 0.4 acre, he could be able to earn Rupees 25,000-30,000 from sweet corn cultivation. Marketing of sweet corn in rural areas remains a critical constraint faced by the farmers like him. Inspired by Majhi, many other farmers are showing interest to cultivate sweet corn. According to Majhi, if government can sort out the marketing issues, more farmers will be motivated to adopt commercial sweet corn cultivation considering the fact that it is one of the most profitable and well suited crop.